Barriers faced by patients in the diagnosis of multidrug-resistant tuberculosis in Brazil - Bhering, Marcela; Dalcolmo, Margareth; Sarubbi Júnior, Vicente; Kritski, Afrânio (Revista de saúde pública, 2022)
OBJECTIVE To understand patients’ narratives about the barriers they faced in the diagnosis and treatment of multidrug-resistant tuberculosis, and their consequences in Rio de Janeiro State, Brazil. METHODS This is a qualitative cross-sectional study with non-probabilistic sampling. A theoretical saturation criterion was considered for composing the number of interviewees. Semi-structured interviews were conducted from August to December 2019 with 31 patients undergoing treatment for multidrug-resistant tuberculosis at an outpatient referral center in Rio de Janeiro. Data were transcribed and processed with the aid of the NVIVO software. Interviews were evaluated by content analysis, and their themes, cross-referenced with participants’ characterization data. RESULTS Our main findings were: a) participants show a high proportion of primary drug resistance, b) patients experience delays in the diagnosis and effective treatment of multidrug-resistant tuberculosis ; c) healthcare providers fail to value or seek the diagnosis of drug-resistant tuberculosis, thus beginning the inadequate treatment for drug-susceptible tuberculosis, d) primary health units show low report rates of active case-finding and contact monitoring, and e) patients show poor knowledge about the disease. CONCLUSIONS We need to improve referral systems, and access to the diagnosis and effective treatment of multidrug-resistant tuberculosis; conduct an active investigation of contacts; intensify the training of healthcare providers, in collaboration with medical and nursing schools, in both public and private systems; and promote campaigns to educate the population on tuberculosis signs and symptoms.